1998
DOI: 10.1097/00004872-199816030-00006
|View full text |Cite
|
Sign up to set email alerts
|

Plasma hydrogen peroxide production in hypertensives and normotensive subjects at genetic risk of hypertension

Abstract: Hydrogen peroxide is produced in blood plasma and elevation of its level could constitute a pathogenic factor in vascular organ damage attendant upon systemic hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
196
0
11

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 324 publications
(220 citation statements)
references
References 50 publications
13
196
0
11
Order By: Relevance
“…148 Additionally, normotensive subjects with a family history of hypertension have greater H 2 O 2 production than blood pressure-matched normotensives without a family history of hypertension, suggesting that there may be a genetic component that leads to elevated production of H 2 O 2 . 149,150 Plasma levels of asymmetric dimethylarginine (endothelial nitric oxide synthase inhibitor) and the lipid peroxidation product of linoleic acid, 13-hydroxyoctadecadienoic acid, a marker of ROS production, were inversely correlated with microvascular endothelial dysfunction and elevated blood pressure in hypertensive patients. To further support a relationship between oxidative stress and blood pressure, Van et al 151 recently showed that myeloperoxidase is positively and independently associated with blood pressure and that this association is strongest in subjects with increased levels of oxidative markers.…”
Section: Ros and Vascular Biology In Hypertensionmentioning
confidence: 99%
“…148 Additionally, normotensive subjects with a family history of hypertension have greater H 2 O 2 production than blood pressure-matched normotensives without a family history of hypertension, suggesting that there may be a genetic component that leads to elevated production of H 2 O 2 . 149,150 Plasma levels of asymmetric dimethylarginine (endothelial nitric oxide synthase inhibitor) and the lipid peroxidation product of linoleic acid, 13-hydroxyoctadecadienoic acid, a marker of ROS production, were inversely correlated with microvascular endothelial dysfunction and elevated blood pressure in hypertensive patients. To further support a relationship between oxidative stress and blood pressure, Van et al 151 recently showed that myeloperoxidase is positively and independently associated with blood pressure and that this association is strongest in subjects with increased levels of oxidative markers.…”
Section: Ros and Vascular Biology In Hypertensionmentioning
confidence: 99%
“…Previous studies have demonstrated increased vascular smooth muscle cell O 2 ·-levels with H 2 O 2 exposure . In addition, increases in systemic plasma H 2 O 2 levels have been observed in patients with cardiovascular disease (Lacy et al 1998). Oxidative stress and increased ROS are associated with multiple cardiovascular disease states.…”
Section: Cardiovascular Disease and Oxidative Stressmentioning
confidence: 99%
“…Although plasma level of H 2 O 2 is usually at the nanomolar level (Lacy et al, 1998), local vascular concentration of H 2 O 2 may be much higher. According to Schraufstatter & Cochrane (1997), local concentration of superoxide (which can be rapidly converted to H 2 O 2 by superoxide dismutase) can reach 5-10 mM when polymorphonuclear leukocytes are stimulated.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with uncontrolled hypertension showed a higher level of ROS (superoxide and hydrogen peroxide, H 2 O 2 ), and effective control of high blood pressure also lowered the high level of ROS to normal level (Prabha et al, 1990). Even among the normotensives, persons with a family history of hypertension exhibited a higher plasma H 2 O 2 level than those without such a family history (Lacy et al, 1998). In the spontaneously hypertensive rats (SHR), a widely used animal model of human essential hypertension, a higher level of ROS and lipid peroxidation in mesenteric arterioles and myocardium was reported (Ito et al, 1992;Suzuki et al, 1995).…”
Section: Introductionmentioning
confidence: 99%